19F oximetry with semifluorinated alkanes - Kegel, Stefan; Chacón-Caldera, Jorge; Tsagogiorgas, Charalambos; Glatting, Gerhard; Schad, Lothar R. (Artificial cells, nanomedicine, and biotechnology, 2016)
This work examines the variation of longitudinal relaxation rate R1(= 1/T1) of the 19F-CF3-resonance of semifluorinated alkanes (SFAs) with oxygen tension (pO2), temperature (T) and pH in vitro. Contrary to their related perfluorocarbons (PFCs), SFA are amphiphilic and facilitate stable emulsions, a prerequisite for clinical use. A linear relationship between R1 and pO2 was confirmed for the observed SFAs at different temperatures. Using a standard saturation recovery sequence, T1 has been successfully measured using fluorine 19F-MRI with a self-constructed birdcage resonator at 9.4 T. A calibration curve to calculate pO2 depending on T and R1 was found for each SFA used. In contrast to the commonly used PFC, SFAs are less sensitive to changes in pO2, but more sensitive to changes in temperature. The influence of pH to R1 was found to be negligible.
Gesehen am 30.10.2019
Die Zahl 19 im Titel ist hochgestellt
Published online 24 November 2015